Szolgáltató centrumok az Északnyugat–Dunántúlon - Nagy, Erika (Tér és Társadalom, 1997)
The county seats of the region (Győr, Szombathely, Veszprém and Zalaegerszeg) and its two towns with county rank (Sopron and Nagykanizsa), by their institutions and economic organisations working in the service sector, have attraction and spatial connections covering the whole counties or reaching over the county borders. It is this sector where the division of functions among the counties is typical. The preliminaries are worth examining back at the turn of the century. Later the urban network of the region, due to the differentiated growth, was more strongly divided: Győr got to the peak of the settlement hierarchy by the growth of its population and the boom in its functions. Also, Szombathely showed a more rapid growth than the average of the towns in the region. This process started as soon as between the two world wars. The growth in the population, however, was the fastest in the 1960s, simultaneously the functions of the towns expanded, too. The booming development of the service sector in the 1960s was mainly due to the expanding of the network of institutions (secondary and higher education, research and cultural institutions), i.e. the public services. This was followed by the transition of the employment structure in the 1970s and 1980s, which most profoundly affected Győr, Veszprém and Sopron. After the increase of the 1970s and 1980s, a decline in the role of public services is expected in the 1990s. This process has not only started in the institutional types of services (education, health care, social sphere) but can also be seen in activities securing the functioning of the settlements. The difficulties in the financing of the services strike in the first place the small and medium size towns and the villages, which have less institutions (primary education). This will reinforce the processes of concentration in this sector. Business services as new elements in the service sector are concentrated in the centres of economic decision making and institutional services. The indices of the economic activity are the most favourable in the county seats, primarily in Győr, thus the growth of this sector will probably be the most dynamic in these settlements. Services promoting economic activity, which require daily contact (legal, accounting, management and tax consultancy), only appeared, however, in a few small and medium size towns, namely in those which are well endowed with institutions or special roles. The deconcentration trends of the services that follow the spatial distribution of the population (trade, personal services) have slowed down during the past two years, as the boom of business foundations has come to an end. The present distribution can be largely modified by the organisational concentration which started in trade, and by the appearance of the international business chains which started the construction of large shopping centres and department stores. This process in Hungary is the fastest in Nortwest Transdanubia, after Budapest.